THE EXISTENCE OF THE ABOGE ISLAMIC JAVANESE DATE IN THE SAMIN KLOPODUWUR BLORA COMMUNITY - Khanifah, Millatul (Fakultas Syari'ah dan Hukum UIN Walisongo, 2023)
The Aboge calendar system is still used today by several traditional Javanese community groups. One community that still uses this calendar system is the Samin Klopoduwur Community, Blora. In contrast to Aboge users who use Aboge to determine the start of the month, this community uses the Aboge calendar as a daily calendar. This research will focus on the existence and factors that encourage the Samin Klopoduwur community to maintain the Aboge Islamic Javanese calendar system. This research is qualitative research using a field approach. Data access was carried out by conducting in-depth interviews, observations and documentation, all of which were analyzed descriptively and analytically. The research results show that apart from being a daily calendar, they also use the Javanese Islamic Aboge calendar system as a guide to determine the days of religious ceremonies.